(untitled) (Journal of humanities and social sciences exploratio, 2026)
Against the backdrop of accelerated globalization and technological revolution, conflict of laws in private international law faces unprecedented challenges in addressing legal conflicts emerging in cross-border antitrust, artificial intelligence (AI) infringement, foreign-related trusts, and intellectual property. This article systematically traces the evolution of conflict of laws from traditional unilateralism towards modern multilateralism, and provides an in-depth analysis of the breakthrough and innovation of the "public law taboo" principle amidst the blurring boundaries between public and private law. Through a comparative analysis of legislative practices and landmark cases in jurisdictions such as the United States, the European Union, and Switzerland, it reveals the significant advantages of the multilateral approach in coordinating transnational legal conflicts and enhancing the fairness and predictability of adjudication. In response to issues such as the fragmented legislation and pronounced unilateral tendencies in judicial practice within China’s conflict of laws system, this article proposes specific recommendations. These include constructing antitrust conflict rules based on the "affected market" connecting factor, adopting a "closest connection" principle for selecting the applicable law in AI infringement cases, and refining the trust property registration system and standards for determining the extraterritorial effect of intellectual property rights. The aim is to provide academic support and referential pathways for the development of a private international law system with Chinese characteristics.